PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU MELALUI PROGRAM IN HOUSE TRAINING DI MADRASAH ALIYAH (MA) NU PUTRA BUNTET PESANTREN CIREBON - Ripai, Ahmad; Iswanto, Pahrul Nur; Munawaroh, Mumun (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to determine the role of school principals in improving teacher competence through an in-house training program at MA NU Putra Buntet Islamic Boarding School, Cirebon Regency. The method used in this research is the descriptive qualitative method through data collection techniques in the form of in-depth interviews, in-depth observation, and documentation studies. Data analysis techniques used are data collection, data reduction, data presentation, and conclusion. Based on the results of this study, the role of the principal is as an educator, manager, supervisor, leader, and motivator. The supporting factors are human resources, IT facilities, and special in-house training rooms. The inhibiting factor is the teacher's motivation, the teacher still uses the old style of teaching, and the teacher's lack of discipline. The results achieved were increasing human resources, improving teacher performance, creating interaction between teachers, increasing motivation, and a sustainable culture.Keywords:The Role of The Peincipal, Teacher Competency , In House Training